Phytochemical Screening and Antibacterial Activity of Methanol Extracts of Indigofera tinctoria - Arini Rajab; Andi Gita Tenri Sumpala; M. Yasser; Subakir Salnus (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
This study aims to identify the secondary metabolite content and evaluate the antibacterial potential of the methanol extract of Indigofera tinctoria leaves. The research was conducted using an exploratory laboratory approach, which involved several key stages sample preparation, ultrasound-assisted extraction with methanol, phytochemical screening, and antibacterial activity testing by the agar disk diffusion method. Phytochemical screening used specific reagents, such as iron (III) chloride, Wagner’s, Dragendorff’s, and Liebermann-Burchard reagents to detect secondary metabolites. The results of the phytochemical analysis showed that the analysis revealed that the methanol extract of Indigofera tinctoria contains various bioactive compounds, including flavonoids, alkaloids, and steroids. Antibacterial activity testing showed the extract inhibited the growth of both gram-positive and gram-negative bacteria. Notably, the extract exhibited the greatest effectiviness against gram-positive bacteria, with the highest inhibition zone recorded in Bacillus subtilis (19.45 mm), followed by Staphylococcus aureus (17.30 mm), Escherichia coli (15.55 mm) and the lowest in Salmonella typhi (8.80 mm). The results suggest that the methanol extract of Indigofera tinctoria leaves processes significant antibacterial activity, particularly against gram-possitive bacteria, and highlight its potential as a source of natural antibacterial agents for future pharmaceutical applications. Further research, including in vivo studies and the isolation of individual compounds, is recommended to understand better the mechanisms involved and to assess the safety and efficacy of Indigofera tinctoria as a therapeutic agent.